Ātmakathā aura upanyāsa : viśesha sandarbha, Bāṇabhaṭṭa kī ātmakathā - Santosha, Jñānendra Kumāra (Radhakrishna Praksahan, 2013)
Study on the Bāṇa Bhaṭṭa kī ātmakathā, novel by Hazariprasad Dwivedi, 1907-1979, Hindi author.